Legacy Report: 2010-2021 - Nutrition Innovation Lab (Tufts University. Tisch Library., 2022)
The following report summarizes the key Nutrition Innovation Lab activities throughout the years and offers key insights and takeaways from the project’s lifetime. The Lab’s contributions to evidence generation, policy strengthening, and capacity building have laid the foundation for scientifically rigorous, systems-level approaches in the nutrition and agriculture spaces for years to come; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy